COMPARATIVE EVALUATION OF DYNAMIC COMPACTION AND RAPID IMPULSE COMPACTION METHOD FOR IMPROVEMENT OF POTENTIALLY LIQUEFIED SAND SOILS AT THE NEW YOGYAKARTA INTERNATIONAL AIRPORT PROJECT - Santi Pratiwi, Desti
The construction of New Yogyakarta International Airport in Kulon Progo Yogyakarta is located at coastal area that has saturated loose sand condition of the soil. Saturated loose sands have a potential of liquefaction when the earthquake is occurs. Soil improvement is needed to reduce the liquefaction potential. The effort that can be taken is compacted the soil using the Dynamic Compaction (DC) and Rapid Impulse Compaction (RIC) methods. DC method has been widely used in common to compacted problematic soil, while RIC is a new method that can be used in Indonesia. However, DC and RIC has the same principle that gave an energy to the ground surface by tamping which is controlled by the weight of the tamper, height of fall, pattern and number of tamping. This thesis aims to evaluate the comparison between DC and RIC methods to increase the soil from liquefaction potential of sand soils in the NYIA Airport Construction area based on field testing data such as SPT and CPT. The improvement area reviewed is runway and terminal. The runway area is improved using DC, while the terminal area is improved by RIC. Comparison of the two methods is done by reviewing the value of the relative density (Dr) of soil in that both areas. The value of relative density is calculated in two condition: the existing conditions and after improvement. The calculations of relative density value was carried by using 3 (three) equations, namely Meyerhof (1956), Yoshida and Ikema (1988), and Kibria and Masood (1998). The results of this study indicate that the increase of relative density value due to DC is more significant compared to the RIC on the soil with a medium dense classification. But in terms of tamping effectiveness on soil improvement at the NYIA Airport Construction, RIC is better to DC because RIC only requires about 1.49 - 2.73 tm/m2 to increase 1% of Dr value, while DC requires energy 1.75 - 20.57 tm/m2.